MEDIUM FREQUENCY ELECTROTHERAPY IN THE MUSCLE STRENGTH (Fiep Bulletin - online, 2019)
Introduction: Neuromuscular electrical stimulation (NMES) has been used as one of the pillars of the therapeutic modalities forthe gain of muscle strength. Objective: To evaluate the strength gain in the elbow flexor muscles in women after the use of NMES.Materials and Methods: 17 women were selected, randomically separated in 2 groups, (Russian Current and Aussie Current).Aussie current was used with the carrier current parameters of 1000Hz, frequency modulated 50Hz, burst of 2 milliseconds andfor the Russian carrier current it was used 2,500 Hz, modulated frequency of 50 Hz, phase (cycle) of 50% both with up and downparameters of 2 seconds, ON and OFF time of 20 seconds, for a total time of 20 minutes in the brachial triceps muscle, withsufficient intensity to provide visible and tolerable muscular contraction, for a period of 5 weeks. The strength measurement wasdone by means of a portable dynamometer. Results: The paired t-test and Student's t-test were used for statistical analysis andthe significance level of p = 0.05 was considered. There was an increase in muscle strength in both stimulated arms, with themean gain in the Aussie group being 10.5 pounds and in the Russian Current group of 14.5 pounds, but there was no statisticallysignificant difference between the electric currents. Conclusion: The two currents were effective in gaining muscle strength andthere was no statistically significant difference in the comparison of them, but the groups were different as to the force at the timepre-stimulation.